2020
DOI: 10.1186/s12936-020-03156-1
|View full text |Cite
|
Sign up to set email alerts
|

A simple monochromatic flow cytometric assay for assessment of intraerythrocytic development of Plasmodium falciparum

Abstract: Background: Gold standard microscopic examination of Plasmodium falciparum intraerythrocytic stage remains an important process for staging and enumerating parasitized erythrocytes in culture; however, microscopy is laborious and its accuracy is dependent upon the skill of the examiner. Methods:In this study, ViSafe Green (VSG), which is a nucleic acid-binding fluorescent dye, was used for assessing in vitro development of P. falciparum using flow cytometry.Results: Fluorescence intensity of VSG was found to d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…TO is a cyanine stain which is based on thioflavin T and it stains primarily RNA [24]. Both stainings, HE and TO, had high efficiency to detect parasites at the blood stage as described in previous study and were confirmed again in this study [26,27].…”
Section: Detection Of P Falciparum-infected Erythrocytes By Flow Cyto...supporting
confidence: 85%
“…TO is a cyanine stain which is based on thioflavin T and it stains primarily RNA [24]. Both stainings, HE and TO, had high efficiency to detect parasites at the blood stage as described in previous study and were confirmed again in this study [26,27].…”
Section: Detection Of P Falciparum-infected Erythrocytes By Flow Cyto...supporting
confidence: 85%
“…To prove the concept, we selected cell-permeant and cell-impermeant fluorophores that emit maximum fluorescence signals at different wavelengths and are applicable for most flow cytometers equipped with common lasers. Previously, our group reported the use of the cell-permeant ViSafe green (VSG) to detect P. falciparum -infected erythrocytes 21 . Given its common use in cell survival tests, the cell-impermeant PI was selected to combine with VSG.…”
Section: Discussionmentioning
confidence: 99%
“…ViSafe Green (VSG) is a cell-permeable fluorophore that was originally used for visualizing separated DNA or RNA on agarose or polyacrylamide gels. Our group demonstrated that VSG could be used to assess the development of P. falciparum in vitro 21 . However, one significant disadvantage of single-use DNA fluorochromes is that they cannot differentiate between viable and dead parasites.…”
Section: Introductionmentioning
confidence: 99%
“…The gDNA of Mansonia spp. or Plasmodium falciparum strain K1 [ 42 ] were used as positive control, respectively. Nuclease-free water was set as the no template control.…”
Section: Methodsmentioning
confidence: 99%